“Efecto in vitro de hipoclorito de sodio y clorhexidina sobre cándida albicans en resina acrílica de termocurado” - Gladys Magdalena, Palomino Villacis (2020)
ABSTRACT: This investigation deals with the evaluation of the In Vitro effect of sodium hypochlorite and chlorhexidine on the strains of Candida albicans in thermosetting acrylic resin. An experimental study was carried out where the entire population; that is, 60 samples, 1 for the positive control (inoculated), 1 for the negative control (without inoculation) Candida albicans strains ATCC 10231. Others were contaminated in TSB and incubated for 48 hours, then they were disinfected with 0.5% sodium hypochlorite and 0.12% chlorhexidine at times of 30 seconds, 1, 2, 5, 10 and 30 minutes and 2% chlorhexidine and hypochlorite of 1% sodium at times of 5, 10 and 30 minutes and then incubating the seeds for 24 to 48 hours for the quantification of colony forming units. The results indicated that sodium hypochlorite in the two concentrations completely eliminates CFUs after 5 minutes and chlorhexidine 0.12% after 10 minutes, unlike 2% chlorhexidine that eliminated all CFUs at 5 minutes. The results showed that there were statistically significant differences between the different concentrations and times of the resin disinfection process with respect to the CFU (p = 0.002). Being sodium hypochlorite the most effective against Candida albicans in relation to chlorhexidine which needs a higher concentration and immersion time to reach its antifungal activity.